2005
DOI: 10.2105/ajph.2004.041616
|View full text |Cite
|
Sign up to set email alerts
|

“Come and Take a Walk”: Listening to Early Head Start Parents on School-Readiness as a Matter of Child, Family, and Community Health

Abstract: We explored the perspectives and experiences of low-income, predominantly African American families regarding children's school-readiness. Our research, which involved qualitative interviews, ethnographic case studies, and "photovoice" methods, focused on families participating in the national evaluation of Early Head Start. While valuing academic skills, study parents emphasized the importance of social and emotional health in regard to both children's and parents' readiness to begin school. These development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 13 publications
3
44
0
3
Order By: Relevance
“…The results demonstrate that while kindergarten teachers felt academic readiness is important, social skills are more important for a child to be successful in school. These findings are similar to other studies on school readiness which have also found the importance of a child being socially and emotionally ready to start school (Lin, Lawrence, & Gorrell, 2003;McAllister, Wilson, Green, & Baldwin, 2005;Piotrkowski, Botsko, & Matthews, 2000;Wesley & Buysse, 2003).…”
Section: School Readiness Definedsupporting
confidence: 91%
See 2 more Smart Citations
“…The results demonstrate that while kindergarten teachers felt academic readiness is important, social skills are more important for a child to be successful in school. These findings are similar to other studies on school readiness which have also found the importance of a child being socially and emotionally ready to start school (Lin, Lawrence, & Gorrell, 2003;McAllister, Wilson, Green, & Baldwin, 2005;Piotrkowski, Botsko, & Matthews, 2000;Wesley & Buysse, 2003).…”
Section: School Readiness Definedsupporting
confidence: 91%
“…The current definitions (initiative, self-control, and attachment) are useful but may not be exact. Also the measures that are used to detect them may not be sensitive enough as yet to capture the true constructs of social and emotional development that most educators still believe significantly predict children's school performance (Johnson, Gallagher, Cook, & Wong, 1995;Lin, Lawrence, & Gorrell, 2003;McAllister, Wilson, Green, & Baldwin, 2005;Piotrkowski, Botsko, & Matthews, 2000;Wesley & Buysse, 2003) Implications This study found that social and emotional development plays a minimal but critical indirect role in the academic achievement of Hispanic children from low-income families. These findings lead to a couple of implications which early childhood educators should take into account.…”
Section: Chapter V Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Diversos estudos nos fornecem experiências, resultados e erros que demonstram que a fotografia participativa pode oferecer resultados inequívocos como qualquer outro instrumento de análise social (GALLO, 2001;MCALLISTER et al, 2005;SPIELMAN, 2001). A intervenção visual, quando não implementada corretamente, pode subestimar o conceito de participação e perpetuar ainda mais o binário estabelecido entre 'silenciar' e o 'dar voz' (LYKES; BLANCHE; HAMBER, 2003).…”
Section: Desafios Dilemas E Constrangimentos Do Método Photovoiceunclassified
“…Para os pesquisadores sociais, o modelo alarga as perspectivas analíticas das investigações e, para os participantes, os benefícios do uso de metodologias visuais colaborativas incluem a validação do repertório de vida e conhecimento local (SPIELMAN, 2001), novas perspetivas sobre si próprios e sua situação (MCINTYRE; THUSI, 2003), aumento da autoestima (EWALD, 2001;BLANCHE;HAMBER, 2003), reforço a equidade de gênero (WILLIAMS;LYKES, 2003), reconhecimento e reflexão enquanto grupo (LYKES; BLANCHE; HAMBER, 2003) e defesa coletiva direcionada para a mudança social (MCALLISTER et al, 2005;WANG;REDWOOD-JONES, 2001). …”
unclassified